Enzyme mediated synthesis of water-dispersible, naturally protein capped, monodispersed gold nanoparticles; their characterization and mechanistic aspects - Khan, Shadab Ali; Ahmad, Absar (RSC Advances, 2014)
Inorganic nanomaterials are conventionally synthesized under harsh environments like extremes of temperature, pressure and pH. These methods are eco-unfriendly, expensive, toxic, cumbersome, yield bigger particles which agglomerate due to not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions viz. room temperature, atmospheric pressure, physiological pH and is reliable, eco-friendly and cheap. We have already reported the extracellular biosynthesis of monodispersed gold nanoparticles from the whole cells of novel extremophilic actinomycete Thermomonospora sp. In order to know the exact mechanism of synthesis, we decided to investigating it further. Here we describe the simple protocol for purification of the temperature and SDS resistant sulfite reductase enzyme and organic capping molecule, which are required for the synthesis and stabilization of gold nanoparticles respectively. This purified enzyme was then employed for the synthesis of gold nanoparticles along with the capping molecule, which render gold nanoparticles monodispersed in solution.

Extracellular biosynthesis of gadolinium oxide (Gd2O3) nanoparticles, their biodistribution and bioconjugation with the chemically modified anticancer drug taxol - Khan, Shadab Ali; Gambhir, Sanjay; Ahmad, Absar (Beilstein Journal of Nanotechnology, 2014)
As a part of our programme to develop nanobioconjugates for the treatment of cancer, we first synthesized extracellular, protein-capped, highly stable and well-dispersed gadolinium oxide (Gd2O3) nanoparticles by using thermophilic fungus Humicola sp. The biodistribution of the nanoparticles in rats was checked by radiolabelling with Tc-99m. Finally, these nanoparticles were bioconjugated with the chemically modified anticancer drug taxol with the aim of characterizing the role of this bioconjugate in the treatment of cancer. The biosynthesized Gd2O3 nanoparticles were characterized by UV-vis spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoemission spectroscopy (XPS). The Gd2O3-taxol bioconjugate was confirmed by UV-vis spectroscopy and fluorescence microscopy and was purified by using high performance liquid chromatography (HPLC).
Keywords: bioconjugation; biodistribution; gadolinium oxide; humicola sp; transmission electron microscopy